Human capital, R&D and Regional export - Urban Gråsjö (European Regional Science Association (ERSA), 2005)
The main purpose in this paper is to study to what extent accessibility to R&D and human capital can explain patent production. Therefore a knowledge production function is estimated both on aggregated level and for different industrial sectors. The output of the knowledge production is the number patent applications in Swedish municipalities from 1994 to 1999. In order to account for the importance of proximity, the explanatory variables are expressed as accessibilities to R&D (university and company) and to human capital (people with a bachelor's degree and above). The total accessibility is then decomposed into local, intra-regional and inter-regional accessibilities. Preliminary findings indicate that the effects are very local, i.e. it is primarily the R&D conducted within the municipality that explains the number of patent applications produced in the municipality. The results also indicate that investments in company R&D have a greater impact on the innovative capacity than university R&D. Furthermore, there is evidence of large scale effects, implying a policy that favour concentrated investments in R&D instead of the dominating trend in Sweden of increased number of localisations/municipalities conducting university R&D.
Keywords: 330